An update on nicotine replacement therapy - K A Kamala; S Sankethguddad; S G Sujith (Wolters Kluwer Medknow Publications, 2019)
Tobacco use is the single greatest preventable cause of death in the world. Most tobacco users want to quit but find it difficult to stop due to the addictiveness of nicotine. Interventions for tobacco cessation are important in enabling tobacco users to stop using, which includes pharmacological and nonpharmacological approaches to aid tobacco cessation. Pharmacological approaches include nicotine replacement therapy (NRT) and nonnicotine medications (bupropion and varenicline). NRT delivers nontoxic forms of nicotine to help tobacco user's deal with nicotine cravings and maintains stimulation of the nicotine receptors. Forms of delivery for NRT include the following: nicotine chewing gum, nicotine lozenge, transdermal patch, nicotine inhaler, nicotine nasal spray, and nicotine sublingual tablets. These NRTs are in general well tolerated and have minimal adverse effects. The present review gives an overview about various modes of NRT methods currently used to treat nicotine dependence.